A novel deep learning model for extracting arable land from high-resolution remote sensing images in hilly areas: a case study in the Sichuan Basin of Southwest China - Yanxi Chen; Xingzhu Xiao; Yongle Zhang; Min Huang; Ziyi Tang; Hao Li (Geocarto International)
Arable land is the fundamental guarantee of agricultural production, and accessing accurate arable land information is particularly crucial. A novel deep learning model named CNX-eMLP with ConvNeXt as the backbone and an enhanced Multilayer Perceptron (eMLP) as the decoder was proposed for arable land extraction. The model was employed to extract arable land using high-resolution satellite imagery in a case study at Pengxi County of Southwest China and compared its performance with six deep learning models, a machine learning-based algorithm, and SinoLC-1. The study results show the CNX-eMLP significantly achieved the highest accuracy, with MIoU and OA of 75.21 and 87.9, highlighting a trade-off between computational complexity and accuracy. The CNX-eMLP model reveals arable land is predominantly found in low-altitude areas (below 400 m), with most plots being 0-5 hectares. The study presents an efficient and feasible method for accurate high-resolution remote sensing monitoring of arable land parcels in hilly regions.